Congenital epulis of the newborn: a case report - Talim, Beril; Yiğit, Şule; Oran, Olcay; Akçören, Zuhal (The Turkish Journal of Pediatrics, 1998)
Congenital epulis of the newborn is a rare benign tumor, also known as a congenital gingival granular cell tumor. Although it is a benign lesion, the tumor may cause feeding and respiratory problems when too large or when multiple tumors exist. In this article, a case of congenital epulis is presented and its treatment is discussed.